Tracing the Power of Tattoos on Malaka-East Nusa Tenggara Women's Bodies during the Japanese Occupation - Eventus Ombri Kaho (Pusat Studi Gender Universitas Jember, 2025)
This study aims to uncover the symbolic meaning and power of tattoos on the bodies of Malacca women in East Nusa Tenggara during the Japanese occupation, from the perspective of Iris Marion Young. In the context of Japanese imperialism, tattoos on the bodies of Malacca women were not merely cultural expressions, but also symbolic media of resistance and expression of identity amidst the pressures of imperialist power and patriarchal control. Young’s approach to structural goals and objectives is applied to examine how women's bodies, through tattoos, become a means of maintaining identity and agency under a system that dominates and controls women. Using in-depth and historical interview methods, this study shows that tattoos play an important role in strengthening women’s resistance to the Japanese power structure. This is motivated by Japan’s actions in making women its sexual objects. This study provides a deeper understanding of how Malacca women use their bodies as a medium of resistance against gender injustice and social inequality.